The effect of preoperative topical magnesium sulfate spraying in the oropharyngeal region on postoperative sore throat following gynecological laparoscopic surgery: a randomized clinical trial - Linxin Wang; Fangfang Li; Yuqing Liu; Xingyu Xiong; Qin Qiu; Guanglei Wang (BMC Anesthesiology)
Abstract Background Postoperative sore throat is a common complication following general anesthesia. This study aimed to investigate the impact of preoperative topical magnesium sulfate spraying in the oropharyngeal region on postoperative sore throat following gynecological laparoscopic surgery. Methods The study included 58 patients scheduled for gynecologic laparoscopic surgery at Xuzhou Medical University Affiliated Hospital. Patients were randomly assigned to either the magnesium sulfate group or the control group, with 29 patients in each group. In the magnesium sulfate group, 25% magnesium sulfate was sprayed at a dose of 15 mg/kg on the mucous membrane of the pharynx and posterior wall of the larynx near the glottis using a laryngoscope under visual guidance during intubation; in the control group, an equal volume of normal saline was used instead. The primary outcome measure was the overall incidence of postoperative sore throat 48 h after surgery. Results The overall incidence of postoperative sore throat in the magnesium sulfate group was lower than that in the the control group (20.0% vs. 66.7%, P < 0.001). At time points T1 (P < 0.001), T2 (P = 0.02), and T3 (P = 0.015), the incidence of postoperative sore throat in the the magnesium sulfate group was also lower than that in the the control group. Conclusion This study confirmed that preoperatively spraying magnesium sulfate locally in the Oropharyngeal Region can reduce the frequency and severity of postoperative sore throat. Trial registration The study was registered at Chictr.org.cn with the number ChiCTR2400087240 on 07/23/2024.